2011
DOI: 10.2147/vhrm.s13552
|View full text |Cite
|
Sign up to set email alerts
|

Critical review of cancer risk associated with angiotensin receptor blocker therapy

Abstract: The role of drugs in new cancer occurrence and cancer-related death is a major concern. Recently, a meta-analysis raised the possibility that angiotensin receptor blockers (ARBs) might have an adverse effect on patients. This generated a significant debate until the publication of two further meta-analyses, neither of which demonstrated an increased risk of new cancer occurrence or cancer-related death with the use of ARBs in patients with hypertension, heart failure, and/or nephropathy. This illustrates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Angiotensin receptor blockers and angiotensin converting enzyme inhibitors are two of the most commonly used antihypertensive agents. Although study findings are conflicting regarding their relation to cancer risk [ 46 - 49 ], the majority of studies conclude that antihypertensive agents do not initiate cancer development [ 37 , 47 , 50 ], and recent studies even suggest a possible inverse association with cancer incidence [ 48 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin receptor blockers and angiotensin converting enzyme inhibitors are two of the most commonly used antihypertensive agents. Although study findings are conflicting regarding their relation to cancer risk [ 46 - 49 ], the majority of studies conclude that antihypertensive agents do not initiate cancer development [ 37 , 47 , 50 ], and recent studies even suggest a possible inverse association with cancer incidence [ 48 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many other retrospective population studies have reported differing effects on cancer risk depending on the cancer type, cohort characteristics, and the RAS inhibitor used. As a result, several meta-analyses have been undertaken (35), again with differing results, which could be due to the nature of the original studies included and inherent publication bias. Aside from the reported effects on cancer risk, many retrospective population studies have also assessed the effect of RAS inhibitors on cancer death.…”
Section: The Renin-angiotensin Systemmentioning
confidence: 99%
“…and resulted in several commentaries and follow up publications. Many of these papers advised caution in interpretation of the results (Sica 2010;Aalbers 2010;Bloch and Basile 2010;Volpe et al 2011;Madsen 2010;Lombard, Nosworthy, and Albers 2010;Marina and Krakoff 2010;Cohen and Townsend 2011); one solid finding from the meta-analysis was a small increase in risk of cancer with ARB/ACEI combination, but no increase in death (Bangalore et al 2011); many studies concluded that there is no significant risk of ARBs worsening cancer incidence or progression (Collaboration 2011;Pasternak et al 2011;Yoon et al 2011;Cassat et al 2011;"No connection between ARBs and cancer" 2011; Olin, Veverka, and Nuzum 2011;Wuerzner, Burnier, and Waeber 2011;Singh and Bangalore 2012) and one highlighting a reduced risk of cancer with ARB use (Huang et al 2011).…”
Section: Angiotensin Mediators Are Clinically Useful In Cancermentioning
confidence: 99%